SOSIALISASI PENGHITUNGAN UNIT COST DAN POLA TARIF RUMAH SAKIT UMUM DAERAH TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Nur Azlina; Muhammad Luthfi iznillah; Edfan Darlis; Al azhar A; Azwir Nasir; Rahmita Budiarti Ningsih; Suci Nurulita; Yusni Maulida (Jurnal Abdi Insani, 2023)
Health services are public services that are the spearhead of public health development. Hospitals as health service providers are required to be able to provide excellent service but on the other hand the rates charged must also be affordable by the community. The problem of service costs is so crucial that it encourages all interested elements to calculate the real cost of services incurred by the hospital. This community service activity aims to socialize Unit Cost Calculation and Tariff Patterns at the Teluk Kuantan Regional General Hospital, Kuantan Singingi Regency. The method of implementing this activity by providing lectures and explanations related to unit cost analysis (Unit Cost) and hospital health service tariff patterns, which in its implementation was carried out with relevant stakeholders for 1 day on June 12, 2023. The results obtained are the implementation of socialization activities for calculating unit costs and tariff patterns at Teluk Kuantan Hospital, which with these activities the Hospital is able to identify the type of service, the character of service products, and costs. This activity is also a reference material in evaluating the applicable tariffs and also as a basis for preparing new tariffs based on unit cost calculations, this activity is also the basis for hospitals to assess performance achievements and the basis for preparing hospital budgets, as well as a pattern of hospital budgeting.